A Substrate-Mimicking Basement Membrane Drives the Organization of Human Mesenchymal Stromal Cells and Endothelial Cells Into Perivascular Niche-Like Structures - Perugini, Valeria; Santin, Matteo (Frontiers in Cell and Developmental Biology, 2021)
Extracellular matrix-derived products (e.g. Matrigel) are widely used for in vitro cell cultures both as two-dimensional (2D) substrates and as three-dimensional (3D) encapsulation gels because of their ability to control cell phenotypes through biospecific cues. However, batch-to-batch variations, poor stability, cumbersome handling, and the relatively high costs strictly limit their use. Recently, a new substrate known as PhenoDrive-Y has been used as 2D coating of tissue culture plastic showing to direct the bone marrow mesenchymal stromal cells (MSCs) toward the formation of 3D spheroids. When organized into 3D spheroids, the MSCs expressed levels of pluripotency markers and of paracrine angiogenic activity higher than those of the MSCs adhering as fibroblast-like colonies on tissue culture plastic. The formation of the spheroids was attributed to the properties of this biomaterial that resemble the main features of the basement membrane by mimicking the mesh structure of collagen IV and by presenting the cells with orderly spaced laminin bioligands. In this study, PhenoDrive-Y was compared to Matrigel for its ability to drive the formation of perivascular stem cell niche-like structures in 2D co-culture conditions of human endothelial cells and adult bone marrow MSCs. Morphological analyses demonstrated that, when compared to Matrigel, PhenoDrive-Y led endothelial cells to sprout into a more consolidated tubular network and that the MSCs nestled as compact spheroids above the anastomotic areas of this network resemble more closely the histological features of the perivascular stem cell niche. A study of the expressions of relevant markers led to the identification of the pathways linking the PhenoDrive-Y biomimicking properties to the acquired histological features, demonstrating the enhanced levels of stemness, renewal potential, predisposition to migration, and paracrine activities of the MSCs.